Changing the dehydrogenation pathway of LiBH4–MgH2via nanosized lithiated TiO2. Issue 11 (25th January 2017) - Puszkiel, J. A.; Castro Riglos, M. V.; Karimi, F.; Santoru, A.; Pistidda, C.; Klassen, T.; Bellosta von Colbe, J. M.; Dornheim, M.
Abstract : Nanosized lithiated titanium oxide (Li x TiO2 ) noticeably improves the kinetic behaviour of 2LiBH4 + MgH2 . Abstract : Nanosized lithiated titanium oxide (Li x TiO2 ) noticeably improves the kinetic behaviour of 2LiBH4 + MgH2 . The presence of Li x TiO2 reduces the time required for the first dehydrogenation by suppressing the intermediate reaction to Li2 B12 H12, leading to direct MgB2 formation.